Large-scale survey to describe acne management in Brazilian clinical practice - Seité S; Caixeta C; Towersey L (Dove Medical Press, 2015)
Sophie Seité,1 Clarice Caixeta,2 Loan Towersey3 1La Roche-Posay Dermatological Laboratories, Asnières, France; 2La Roche-Posay Dermatological Laboratories, Rio de Janeiro, RJ, Brazil; 3AIDS Division, Hospital Municipal Carlos Tortelly, Niterói, RJ, Brazil Background: Acne is a chronic disease of the pilosebaceous unit that mainly affects adolescents. It is the most common dermatological problem, affecting approximately 80% of teenagers between 12 and 18 years of age. Diagnosis is clinical and is based on the patient's age at the time the lesions first appear, and on its polymorphism, type of lesions, and their anatomical location. The right treatment for the right patient is key to treating acne safely. The aim of this investigational survey was to evaluate how Brazilian dermatologists in private practice currently manage acne.Materials and methods: Dermatologists practicing in 12 states of Brazil were asked how they manage patients with grades I, II, III, and IV acne. Each dermatologist completed a written questionnaire about patient characteristics, acne severity, and the therapy they usually prescribe for each situation.Results: In total, 596 dermatologists were interviewed. Adolescents presented as the most common acneic population received by dermatologists, and the most common acne grade was grade II. The doctors could choose more than one type of treatment for each patient, and treatment choices varied according to acne severity. A great majority of dermatologists considered treatment with drugs as the first alternative for all acne grades, choosing either topical or oral presentation depending on the pathology severity. Dermocosmetics were chosen mostly as adjunctive therapy, and their inclusion in the treatment regimen decreased as acne grades increased.Conclusion: This survey illustrates that Brazilian dermatologists employ complex treatment regimens to manage acne, choosing systemic drugs, particularly isotretinoin, even in some cases of grade I acne, and heavily prescribe antibiotics. Because complex regimens are harder for patients to comply with, this result notably raises the question of adherence, which is a key factor in successful treatment. Keywords: acne, management, severity of acne, Brazil